The contract between science and society: A South African case study. (25th May 2018) - Kahn, Michael
Abstract: The anchor concept of this article is the implicit or explicit social contract for science, and its interaction with research and innovation policy in a given system of innovation. This is a topic that has received considerable interest over recent years as innovation, often conflated with the term 'science' has become a buzzword in both the North and South. In order to interrogate the evolution of the social contract for science under conditions of politico-economic change, this contribution examines the case of South Africa in the transition from apartheid to a more inclusive constitutional democracy. The changing social contract is examined through an ideographic methodology conducted through structured interviews with insiders who shaped or implemented research and innovation policy from the 1990s going forward. This contribution extends the analysis of science policy; the process of formulating new policy; and its adoption, modification, and implementation.